2005
DOI: 10.1577/t04-124.1
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Variability in Tissues of Temperate Stream Fishes

Abstract: Previous measurements of stable isotope ratios in fishes have typically used white muscle, but potential applications exist for the use of other tissues. We tested three tissues (liver, fin, and gonad) in three freshwater species (juvenile Atlantic salmon Salmo salar, slimy sculpin Cottus cognatus, and brook trout Salvelinus fontinalis) to investigate potential ecological applications of stable isotopes in tissues other than muscle. Caudal fin tissue correlated closely with muscle tissue for Atlantic salmon an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
101
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 47 publications
17
101
4
Order By: Relevance
“…This was consistent with the findings of Busst et al (2015), who reported the same relationships for wild and laboratory populations of the two model species used here, plus eight other species of the Cyprinidae family. These general patterns were also consistent with those between muscle and fin tissue for chinook salmon Oncorhynchus tshawytscha, brook trout Salvelinus fontinalis, brown trout Salmo trutta, rainbow trout Oncorhynchus mykiss and Atlantic salmon Salmo salar (Pinnegar and Polunin, 1999;Jardine et al, 2005;Sanderson et al, 2009;Graham et al, 2013). Tronquart et al (2012) also showed similar relationships between these tissues for 14 European freshwater fishes.…”
Section: Stable Isotope Values Across Different Tissuessupporting
confidence: 79%
“…This was consistent with the findings of Busst et al (2015), who reported the same relationships for wild and laboratory populations of the two model species used here, plus eight other species of the Cyprinidae family. These general patterns were also consistent with those between muscle and fin tissue for chinook salmon Oncorhynchus tshawytscha, brook trout Salvelinus fontinalis, brown trout Salmo trutta, rainbow trout Oncorhynchus mykiss and Atlantic salmon Salmo salar (Pinnegar and Polunin, 1999;Jardine et al, 2005;Sanderson et al, 2009;Graham et al, 2013). Tronquart et al (2012) also showed similar relationships between these tissues for 14 European freshwater fishes.…”
Section: Stable Isotope Values Across Different Tissuessupporting
confidence: 79%
“…The method of comparing non-destructive and destructive tissue in animals for stable isotope research has yielded successful results with fish (Shannon et al 2001;Johnson et al 2002;Jardine et al 2005;Kelly et al 2006;Sanderson et al 2009), birds , and sea turtles (Seminoff et al 2006), and this study shows this method can work well with other ectothermic vertebrates. Though our results suggest species-specific differences in stable isotope relationships among tissues, we caution that our study cannot resolve whether there were truly species-specific differences.…”
Section: Discussionmentioning
confidence: 79%
“…Small samples of fin tissue were collected from larger predatory fish as recreational anglers typically catch and release these predatory species. Fin clipping was selected because stable isotope values of fins are known to correlate closely with those of muscle tissue in small salmonids and other small fish, allowing a non-lethal sampling for SIA (Jardine et al 2005, Kelly et al 2006, Sanderson et al 2009). However, the validity of fin tissue as a proxy for muscle tissue for much larger fish, such as catfish, has not been previously tested.…”
Section: Studymentioning
confidence: 99%